2022
DOI: 10.1055/s-0042-1750077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pneumatic Transport System on Preanalytical Phase Affecting Clinical Biochemistry Results

Abstract: Introduction PTS (pneumatic transport system) is extensively being used in modern hospitals for rapid transportation of blood samples and other specimens. However, it has a potential impact on blood components, which should be investigated and nullified accordingly. This study was part of a correction program aimed at reducing hemolysis. It was done by comparing paired samples transported manually and by PTS. Materials and Methods This study was initiated to monitor the impact of PTS on hemolysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…On the other hand, specimens collected from a limited group of population were the limitation of most studies. To cite, samples from mostly healthy volunteers or patients may not truly assess the effects of the PTS [ 3,9,11,14,16,17,18]. Contrarily, samples from terminally ill patients may give erroneous results when subjected to PTS [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, specimens collected from a limited group of population were the limitation of most studies. To cite, samples from mostly healthy volunteers or patients may not truly assess the effects of the PTS [ 3,9,11,14,16,17,18]. Contrarily, samples from terminally ill patients may give erroneous results when subjected to PTS [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, some studies stated that restricting their analysis on the effects of PTS as their limitation. For instance, analyzing only the hemolysis-sensitive and platelet-speci c tests despite the possibility that other laboratory variables may be associated with the acceleration forces of PTS in various ways [9] and measuring only the speci c analytes sensitive to hemolysis [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven research studies [1,2,4,5,6,8,9,10,11,13,15] investigated the impact of PTS on potassium levels. Statistically signi cant differences were found in ve studies [1,4,8,9,11 ] with p-values of 0.001, 0.0, 0.002, 0.042, and < 0.02, respectively.…”
Section: Potassium (K)mentioning
confidence: 99%
“…Out of seven studies [4,5,6,9,11,12,18], only one study [6] however, the study showed an increase in hemolysis index and was considered signi cant. The study of Wang et al showed the longest length of PTS was used with a measurement of 1000 m, while two studies did not report the length of PTS.…”
Section: Hemolysis Indexmentioning
confidence: 99%